Monowave-Assisted Optimization of Transesterification for Sustainable Biodiesel Production from Sterculia foetida Oil - Zaki Aqila; Zhafa Aulia Pawisty; Adri Rakha Sebayang; Dodi Tri Nugraha Winandar; Syarafina Hanifah; Deswita; Fayaz Hussain (Politeknik Negeri Medan, 2026)
This study presents a comprehensive optimization of biodiesel production from Sterculia foetida oil using monowave irradiation. Response Surface Methodology (RSM) based on a Box–Behnken design was employed to evaluate the effects of key process variables, including methanol-to-oil ratio, catalyst loading, reaction time, and irradiation conditions, on biodiesel yield. The results demonstrated that monowave irradiation significantly enhances heat transfer, accelerates reaction kinetics, and reduces processing time compared to conventional methods. Biodiesel conversion yields ranged from 83.55 % to 97.22 %, meeting the requirements of ASTM D6751 and EN 14214 standards. The developed quadratic model showed a high coefficient of determination (R² = 98.57 %), indicating strong model reliability. Analysis of variance (ANOVA) revealed that methanol-to-oil ratio, catalyst concentration, and irradiation time were the most significant factors affecting methyl ester yield. The optimal conditions were identified at a methanol-to-oil ratio of 55.45 %, catalyst concentration of 0.884 wt%, agitation speed of 650 rpm, irradiation time of 7.55 min, and reaction temperature of 100 °C, resulting in a maximum biodiesel yield of 97.4 %. These findings confirm that monowave-assisted transesterification is an effective, energy-efficient, and cost-effective approach for sustainable biodiesel production from non-edible feedstocks.